Grafeno interagindo com agrotóxicos: um estudo DFT - OLIVEIRA, Andreik Pereira de (2023)
Pesticides are widely used around the word, especially in less developed contries. These products, whose objective is to eliminate insects in plantations, infiltrating the soil, groundwater and the rainwater, which, wen flowing therough the plantations, transport the pesticides to the rivers, contaminating the waters and aquatic beings. So, is necessary to detect and remove these toxic substances from the environment. In this work we analyze the interaction of acephate and glyphosate pesticides with graphene through firts prınciples calculations, based on the density functional theory, implemented in the Siesta computer program. It was observed through the binding energy that both acephate and glyphosate interact with graphene through a physical process in all configurations considered for analysis. Thus, we propose that graphene is a possible candidate to be used as a filter to remove the pesticides acephate and glyphosate from the aquatic environment due to physical interaction.